The Art of Embroidery: Integrating Design and Technique in Smart Casual Apparel - Gadi, Alicia Christy Zvereva; Triyanto, Triyanto; Warno, Kusminarko (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This research discusses the exploration of the design and application of combination embroidery applied as decoration on smart casual clothing, as well as the level of interest of potential users, both industry and consumers of this embroidery. This type of research is descriptive and explorative with a survey approach. The data collection method used an expert panelist test and a prospective consumer panelist test equipped with rating sheets and questionnaires. The test samples were made of 4 smart casual fashion products by applying the combination embroidery technique as the design accent. The data sources of this research were lecturers, employees, and female students at UNY, as well as prospective users from the fashion industry, in the age category of teenagers to early adults, with a total of 128 respondents, taken through a purposive sampling technique. Data analysis used descriptive techniques with percentages. The results of this study are: 1) stabilization of the design concept of combination embroidery applied as decoration on smart casual clothing at several points of clothing details with symmetrical and asymmetrical concepts, 2) respondents' responses to the application of asymmetrical concepts were very high category of 93.75%, and respondents' responses to the application of symmetrical concepts were very high category of 82.03%.